Cooperative-Based Empowerment of Women in Timor-Leste: A Conceptual Model - Hindah Mustika; Susanti; Mateus Ximenes (Institut Riset dan Publikasi Asas Nusantara., 2026)
Women's economic participation in rural Timor-Leste remains constrained by unequal access to productive resources, limited institutional support, and persistent socio-cultural norms, despite the potential of cooperatives to address these barriers. Existing literature discusses gender equality, entrepreneurship, and cooperative development largely in isolation, leaving a theoretical gap in explaining how cooperative participation translates into women's economic empowerment in Timor-Leste's four municipalities: Dili, Baucau, Maliana, and RAEOA. This conceptual paper synthesizes gender and economic empowerment theory with cooperative institutional theory to propose a model in which cooperative participation comprising governance involvement, resource access, and collective bargaining mediates the relationship between structural antecedents (resource access, institutional support, socio-cultural norms) and empowerment outcomes (income, decision-making capacity, social welfare), moderated by regional context. The model offers a theoretical foundation for future empirical validation and practical guidance for cooperative institutions, policymakers, and development agencies.